The Figure‐of‐Eight Artifact in the Echocardiographic Assessment of Percutaneous Disc Occluders: Impact of Imaging Depth and Device Type. Issue 3 (22nd July 2014) - Bertrand, Philippe B.; Grieten, Lars; Smeets, Christophe J.P.; Verbrugge, Frederik H.; Mullens, Wilfried; Vrolix, Mathias; Rivero‐Ayerza, Maximo; Verhaert, David; Vandervoort, Pieter M.
<x xml:space="preserve">Abstract</x> Purpose Echocardiography is increasingly important in the guidance and follow‐up of percutaneous transcatheter device closures. It was recently shown that the Amplatzer left atrial appendage occluder frequently presents as a figure‐of‐eight artifact due to interaction of device mesh and ultrasound waves. It remains unknown whether this can be translated to other types of disc occluders. Furthermore, the morphology of this figure‐of‐eight artifact appears to be different in the transesophageal and transthoracic image of the same device. The aim of this study was to evaluate the echocardiographic appearance of different types of disc occluders, and to clarify differences in morphology of the figure‐of‐eight artifact. Methods A mathematical model of an epitrochoid curve was used for numerical simulation of disc occluder appearance at various imaging depths. In addition, an in vitro setup was used for echocardiographic analysis of different types of disc occluders at adjustable imaging depth and position. Results Mathematically, decreasing the imaging depth resulted in a more asymmetric figure‐of‐eight, i.e. with small upper part and wide lower part. In vitro results were in close agreement with the mathematical results. In addition, in vitro a figure‐of‐eight artifact was obtained in all different types of disc occluder devices. Conclusions Different types of percutaneous disc occluders all present as a figure‐of‐eight artifact on echocardiography when imaged from a coronal imaging position. The morphology of the artifact depends on the imaging depth, with a more asymmetric figure‐of‐eight morphology at smaller probe‐to‐device distance. This clarifies the differences observed between transesophageal and transthoracic imaging.